Santripreneurs: The Rise of Islamic Innovators in Business, Science, and Technology - Pratiwi; Dwi Atmodjo; Farah Kaylila; Sae Katami; Rina Hudaini (Proceeding of International Conference on Islamic Boarding School, 2025)
Students who become change agents in various domains, such as business, science, and technology, are known as santripreneurs. They act as innovators who integrate Islamic values ​​with an entrepreneurial spirit and the use of modern technology. Social santripreneurs contribute by developing sharia economics, halal fintech, and digital-based startups based on Islamic ethical principles in the business world. In addition, they also utilize artificial intelligence for education and preaching. This study explores the role of santri as drivers of innovation in the digital era with a qualitative approach through literature studies and phenomenological analysis. The study results show that Islamic boarding schools have great potential as centers of innovation that integrate religious knowledge with technological developments. The conclusion of this study emphasizes the importance of increasing santri’s access to digital literacy, entrepreneurship training, and collaboration with various stakeholders to encourage an inclusive and sustainable innovation ecosystem.